Clinical Effectiveness of Weight Loss and Weight Maintenance Interventions for Men: A Systematic Review of Men-Only Randomized Controlled Trials (The ROMEO Project). (July 2017) - Robertson, Clare; Avenell, Alison; Stewart, Fiona; Archibald, Daryll; Douglas, Flora; Hoddinott, Pat; van Teijlingen, Edwin; Boyers, Dwayne
Men are underrepresented in obesity services, suggesting current weight loss service provision is suboptimal. This systematic review evaluated evidence-based strategies for treating obesity in men. Eight bibliographic databases and four clinical trials' registers were searched to identify randomized controlled trials (RCTs) of weight loss interventions in men only, with mean/median body mass index of ≥30 kg/m 2 (or ≥28 kg/m 2 with cardiac risk factors), with a minimum mean/median duration of ≥52 weeks. Interventions included diet, physical activity, behavior change techniques, orlistat, or combinations of these; compared against each other, placebo, or a no intervention control group; in any setting. Twenty-one reports from 14 RCTs were identified. Reducing diets produced more favorable weight loss than physical activity alone (mean weight change after 1 year from a reducing diet compared with an exercise program −3.2 kg, 95% confidence interval −4.8 to −1.6 kg, reported p < .01). The most effective interventions combined reducing diets, exercise, and behavior change techniques (mean difference in weight at 1 year compared with no intervention was −4.9 kg, 95% confidence interval −5.9 to −4.0, reported p < .0001). Group interventions produced favorable weight loss results. The average reported participant retention rate was 78.2%, ranging from 44% to 100% retention, indicating that, once engaged, men remained committed to a weight loss intervention. Weight loss for men is best achieved and maintained with the combination of a reducing diet, increased physical activity, and behavior change techniques. Strategies to increase engagement of men with weight loss services to improve the reach of interventions are needed.